An Analysis of Libby Day’s Personality in Gillian Flynn’s Dark Places Novel: Analisis Kepribadian Libby Day dalam Novel Dark Places karya Gillian Flynn - Warjaya, Wahyu; Alamsyah, Alamsyah (Jurnal Riseta Soshum, 2025)
This study aims to explain how the Id, Ego and Superego are portrayed in the main character in the novel Dark Places by Gillian Flynn using Sigmund Freud's psychological theory. This  method uses qualitative and the data was taken from the narrative and dialogue related to Libby Day as the main character in the novel. The findings of this study showed that the portrayal of Libby Day as the main character has an unbalanced psychological aspect. The Id in itself is described as more dominant with 10 data than the other two psychological aspects, namely the Ego and Superego, each of which has 3 data. This dominant Id aspect triggers her to be lacking empathy, self-centered, often stealing and cheating when facing difficult situations where the imbalance will have a negative impact on herself and others. However, behind that, it is portrayed that there is still an ego in her that is willing to open her old wounds in order to get money and clear the bad name of her brother who was slandered, and gradually her Ego develops into a Superego where she didn't want her family to experienced difficulties because of her.